Banking and debt crisis in Europe: The dangerous liaisons? - Bertrand Candelon; Franz Palm (Center for Economic Studies and ifo Institute (CESifo), 2010)
The potential mutation of the Sub-Prime banking crisis into a sovereign debt one in Euro area countries is investigated. After reviewing the criteria used to measure the debt vulnerability, the balance sheet approach (BSA) is presented in order to illustrate the potential connections between these two types of crises. A graphical analysis yields evidence that at the end 2009 the probability of observing a Euro area country defaulting is less likely than six month before. Nevertheless, the serious threats, which concern Greece and Ireland, do not permit us to exclude the occurrence of a contagious, or self-fulfilling, sovereign debt or currency crises in Euro area in the future.
Keywords: E32; F36; 330; king crisis; sovereign debt crisis; European Union; Öffentliche Schulden; Länderrisiko; Währungskrise; Euro; Bankenkrise; Finanzmarktkrise; Eurozone